(untitled) (Analysis in Theory and Applications, 2024)
We construct examples of twice differentiable functions in R^n with continuous Laplacian and bounded discontinuous Hessian. The same construction is also applicable to higher order differentiability, the Monge-Ampère equation, and the mean curvature equation for hypersurfaces.